Salary and career snippets revelation #2 : Accountancy possibilities, perspectives and purpose - GOH, Clarence (Institutional Knowledge at Singapore Management University, 2024)
Complementing the insights shared in Snippets Revelation #1, this report explored the multiple pathways, progression and prospects of a career in accountancy, it delve deeper into the possibilities, perspectives and purpose of the profession. In this second instalment, the Institute of Singapore Chartered Accountants (ISCA), through its Salary and Career Review Taskforce, worked in collaboration with Singapore Management University’s (SMU) School of Accountancy to further examine salary trends and how it compares to other professions. In addition to these insights, Snippets Revelation #2 offers a unique perspective from accountancy professionals in Singapore. Through their personal experiences, they share how they navigated their career paths, the challenges they encountered, and the strategies that led to their success. This second revelation aims to provide a richer understanding of the diverse opportunities available and the perspectives of those in the profession. It would serve as a useful resource for students, educators, and parents to better understand the accountancy landscape in Singapore. In addition, this report will provide students with meaningful insights into accountancy as a potential career choice.